All-Optical Assay to Study Biological Neural Networks - Afshar Saber, Wardiya; Gasparoli, Federico M.; Dirks, Marjet G.; Gunn-Moore, Frank J.; Antkowiak, Maciej (Frontiers in Neuroscience, 2018)
We introduce a novel all-optical assay for functional studies of biological neural networks in vitro. We created a novel optogenetics construct named OptoCaMP which is a combination of a channelrhodopsin variant (CheRiff) and a red genetically encoded calcium indicator (jRCamp1b). It enables simultaneous optical stimulation and recording from large population of neurons with single-cell readout. We also developed a spatio-temporal all-optical assay to simultaneously stimulate a sub-section of a neural network and record evoked calcium activity, in both stimulated and non-stimulated neurons, thus allowing the investigation of the spread of excitation through an interconnected network. Finally, we demonstrate the sensitivity of this assay to the change of neural network connectivity.